A pilot investigation of a brief, needs‐led caregiver focused intervention in psychosis. Issue 4 (1st September 2014) - Roddy, Sarah; Onwumere, Juliana; Kuipers, Elizabeth
Abstract : Caregivers play an important role in the treatment and recovery of people with psychosis but they have different needs from service users and can experience significant distress as part of their role. Responding to caregiver needs is not readily identified as being the primary responsibility of clinical services that have limited resources. A small pilot study sought to evaluate the effect and acceptability of providing a brief, needs‐led intervention to long‐term caregivers of service users with psychosis. A two or three session, interactive and structured intervention, adapted from family work with psychosis, focused on facilitated carer access to reliable information about psychosis, goal setting and adaptive problem‐solving. Measures of affect, coping and care‐giving impact were completed at baseline and post‐intervention. Data for the first four caregivers who attended individual sessions are presented. Post‐intervention scores indicate reductions in levels of carer distress and depressive symptoms. Caregivers reported high levels of acceptability and satisfaction. Further studies are required to evaluate the impact of such interventions on a larger number and wider range of caregivers. Practitioner points: To date, it has proved difficult for clinical services to meet the needs of caregivers of service users with psychosis. The caregivers of service users with psychosis have readily identifiable needs that can be met with a brief, structured, individualized and interactive intervention. Offering a time‐limited intervention to carers who would like support with their role has benefits for both the caregivers and the service.